Field oriented control based on a 24-sector vector space decomposition for dual three-phase PMSM applied on electric ship propulsion - Mhammed Hasoun; Aziz El Afia; Mohamed Khafallah; Karim Benkirane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
A Field Oriented Control (FOC) strategy based on a 24-Sector Vector  Space Decomposition (24SVSD) technique used to control a Dual Three-Phase Permanent Magnet Synchronous Motor (DTP-PMSM) applied on electric ship propulsion prototype is presented in this paper. This machine is supplied by Dual Three-Phase Voltage Source Inverter (DTP-VSI). This study carried out on these multiphase machines has revealed that the large zero sequence harmonic current components on (z1, z2) subspace, constitutes major drawbacks; despite their advantages. The machine’s dynamic model is accomplished in three two-dimensional and orthogonal subspaces. In order to reduce more extra stator harmonic currents that produces losses, the current work is also concering of to consider the three different approaches for the sake of boosting the machine’s efficiency. Thus, the principle selection of the reference voltage vector and the time calculation method are presented in details. The proposed strategy effectiveness is validated by simulation results.